Sampling for stereology in lungs - J. R. Nyengaard; H. J. G. Gundersen (European Respiratory Review, 2006)
The present article reviews the relevant stereological estimators for obtaining reliable quantitative structural data from the lungs. Stereological sampling achieves reliable, quantitative information either about the whole lung or complete lobes, whilst minimising the workload. Studies have used systematic random sampling, which has fixed and constant sampling probabilities on all blocks, sections and fields of view. For an estimation of total lung or lobe volume, the Cavalieri principle can be used, but it is not useful in estimating individual cell volume due to various effects from over- or underprojection. If the number of certain structures is required, two methods can be used: the disector and the fractionator. The disector method is a three-dimensional stereological probe for sampling objects according to their number. However, it may be affected on tissue deformation and, therefore, the fractionator method is often the preferred sampling principle. In this method, a known and predetermined fraction of an object is sampled in one or more steps, with the final step estimating the number. Both methods can be performed in a physical and optical manner, therefore enabling cells and larger lung structure numbers (e.g. number of alveoli) to be estimated. Some estimators also require randomisation of orientation, so that all directions have an equal chance of being chosen. Using such isotropic sections, surface area, length, and diameter can be estimated on a Cavalieri set of sections. Stereology can also illustrate the potential for transport between two compartments by analysing the barrier width. Estimating the individual volume of cells can be achieved by local stereology using a two-step procedure that first samples lung cells using the disector and then introduces individual volume estimation of the sampled cells. The coefficient of error of most unbiased stereological estimators is a combination of variance from blocks, sections, fields of view, and noise due to random positioning of the probes. This can be decreased by increasing the number of units from the element causing the most variance. Overall, stereology provides lung scientists with efficient tools for estimating structural components correctly.